Mechanically excellent nacre-inspired protective steel-concrete composite against hypervelocity impacts - Yong Mei (Nature Portfolio, 2021)
Abstract Steel–concrete (SC) composite widely used in military defensive project is due to its impressive mechanical properties, long-lived service, and low cost. However, the growing use of hypervelocity kinetic weapons in the present war puts forward higher requirements for the anti-explosion and penetration performance of military protection engineering. Here, inspired by the special ‘brick-and-mortar’ (BM) structural feature of natural nacre, we successfully construct a nacre-inspired steel–concrete (NISC) engineering composite with 2510 kg/m3, possessing nacre-like lamellar architecture via a bottom-up assembling technique. The NISC engineering composite exhibits nacreous BM structural similarity, high compressive strength of 68.5 MPa, compress modulus of 42.0 GPa, Mohs hardness of 5.5, Young’s modulus of 41.5 GPa, and shear modulus of 18.4 GPa, higher than pure concrete. More interestingly, the hypervelocity impact tests reveal the penetration capability of our NISC target material is obviously stronger than that of pure concrete, enhanced up to about 46.8% at the striking velocity of 1 km/s and approximately 30.9% at the striking velocity of 2 km/s, respectively, by examining the damages of targets, the trajectories, penetration depths, and residual projectiles. This mechanically integrated enhancement can be attributed to the nacre-like BM structural architecture derived from assembling the special steel-bar array frame-reinforced concrete platelets. This study highlights a key role of nacre-like structure design in promoting the enhanced hypervelocity impact resistance of steel–concrete composites.